PENGARUH PROFITABILITAS DAN UKURAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN MANUFAKTUR SEKTOR FARMASI YANG TERDAFTAR DI BEI PERIODE 2019-2023 - Lestari, Dini Martinda; Afriani, Raden Irna; Asih, Mila (Yayasan Education and Social Center, 2025)
Company value is one thing that can see the success of a company, profitability and company size are factors that can determine whether the company value is good or not. This research aims to determine the effect of profitability and company size on company value in pharmaceutical sector manufacturing companies listed on the IDX for the 2019-2023 period. The research method used is descriptive quantitative, using a purposive sampling technique with a population of 10 companies while the sample is 9 companies with a 5-year observation period so that the total data is 45 data processed with SPSS Version 26. The results of testing the first hypothesis (H1) significance value = 0.000 < 0.05 or sig value <0.05 and tcount = 4.307 with ttable = 2.01 or tcount>ttable then Ha is accepted H0 is rejected (H2) significance value = 0.025 < of 0.05 or sig value <0.05 and tcount = 2.303 with ttable = 2.01 or tcount>ttable then Ha is accepted H0 is rejected (H3) the significance value is 0.000 <0.05 or sig <0.05 and the Fcount value >Ftable or Fcount = 15.183 and Ftable = 3.22 then Ha is accepted H0 is rejected The conclusion of this research shows that profitability has an effect on company value. Company size influences company value. Profitability and company size simultaneously influence company value